The Current State of Malaysia’s Journey towards a Green Economy: The Perceptions of The Companies on Environmental Efficiency and Sustainability - Abdullah, Hussin; Bakar, Nor’Aznin Abu; Jali, Mohd Razani Mohd; Ibrahim, Fatimah Wati (International Journal of Energy Economics and Policy, 2017)
Malaysia is committed to fostering the development of a clean and efficient economy; that is, a “green” economy. This means encouraging the development of green businesses and green products, which in turn will create “green jobs”. The current economic and environmental crises have accelerated during the last two decades: global warming in climate; fuel, food, water and the economy as a whole. At the fundamental level, there exists a misallocation of resources. Relatively little capital was invested in energy efficiency, sustainable agriculture, ecosystem, land and water conservation. This pattern of development and growth has had detrimental impacts on the well-being of current generations and presents risk and challenges for future generations. As Malaysia promotes greater environmental awareness, it is important to establish national benchmarks by which to measure progress toward a greener economy. This study seeks to advance the state of knowledge in Malaysia on the green economy. To achieve this we need to be able to measure resources, economic activity and progress, accurately and appropriately. The result also indicates that an increase in the prioritising green economy projected by the companies operating in Malaysia will lead to increase in green economic sustainability. This implies that the progress towards the green economy in Malaysia is also influenced by the perception of its importance in the future. The analysis reveals that increase in green economy awareness among the firms will lead to increase in the level of environmental sustainability, thereby improving the current state of green economy in Malaysia. Moreover, an increase in the green economy priority by the companies increases its sustainability in the economy. Keywords: Green economy; environmental efficiency; Sustainability; Perceptions of the companies JEL Classifications: Q56, Q58